Pengaruh Penerapan Model Contextual Teaching And Learning (CTL) terhadap Hasil Belajar Kognitif Siswa dalam Pembelajaran Matematika Kelas IV SDN 01 Rasau Jaya - Ira Rahmawati; Budiman Tampubolon; Asmayani Salimi (Journal on Education, 2024)
This research aims to analyze the influence of applying the Contextual Teaching and Learning (CTL) model on students cognitive learning outcomes in class IV mathematics learning of SDN 01 Rasau Jaya. The research method used is experimental method in the form of quasi experimental design with nonequivalent control group design. The population of this research were all class IV students totaling 34 students. The sampling technique used is total sampling technique. The data collection technique used is measurement technique. The data collection instrument used is test with written test type. Based on the results of data analysis, the average value in the experimental class was 80, while the control class was 71.33. Based on the results of the t-test, the value of , while the value of . It is known that meaning Ho is rejected while Ha is accepted. Based on the results of the calculation of effect size (ES), the value of ES = 0.53 which is included in the medium category. It can be concluded that the application of the Contextual Teaching and Learning (CTL) model has medium influence on students cognitive learning outcomes in class IV mathematics learning of SDN 01 Rasau Jaya.